2016
DOI: 10.1177/0300060516638990
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism 2184A/G in the AGER gene is not associated with diabetic retinopathy in Han Chinese patients with type 2 diabetes

Abstract: ObjectiveTo assess the association between the 2184A/G polymorphism in the advanced glycosylation end product-specific receptor (AGER) gene and the susceptibility to diabetic retinopathy (DR) in Han Chinese patients with type 2 diabetes mellitus (T2DM).MethodsThis cross-sectional genotyping study included patients with T2DM with and without DR. Genotype and allele frequencies of the 2184A/G polymorphism were detected using polymerase chain reaction–restriction fragment-length polymorphism analysis.ResultsThis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…An Indian study on type 2 diabetes has shown significant associations between rs2070600 and diabetic retinopathy [39]. Significant associations between rs2070600 with diabetic retinopathy were also reported in Asian Indians and Asian Chinese with type 2 diabetes [40]. A study in Ashkenazi or Sephardic Jewish patients with type 1 or type 2 diabetes established that rs2070600 was associated with the risk of developing diabetic nephropathy [41].…”
Section: Rs2070600 Nm_0011364:c244g>a Pgly82ser Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…An Indian study on type 2 diabetes has shown significant associations between rs2070600 and diabetic retinopathy [39]. Significant associations between rs2070600 with diabetic retinopathy were also reported in Asian Indians and Asian Chinese with type 2 diabetes [40]. A study in Ashkenazi or Sephardic Jewish patients with type 1 or type 2 diabetes established that rs2070600 was associated with the risk of developing diabetic nephropathy [41].…”
Section: Rs2070600 Nm_0011364:c244g>a Pgly82ser Polymorphismmentioning
confidence: 99%
“…But they did not find any causal link between renal function and rs2070600, even if rs2070600 was associated with sRAGE levels [48]. The lack of a significant association between rs2070600 and diabetic retinopathy has been reported in both Malaysian and Japanese populations [40]. A meta-analysis did not show any significant association between rs2070600 and increased risk of diabetes [49].…”
Section: Rs2070600 Nm_0011364:c244g>a Pgly82ser Polymorphismmentioning
confidence: 99%
“…Li et al. () investigated the SNP rs3134940 in their Chinese cohort, but did not find an association with DR.…”
Section: Chronic Hyperglycaemiamentioning
confidence: 97%
“…Hyperglycemia induced ROS overproduction is mediated by AGEs interaction with its receptors like AGE-R1 (oligosaccaharyl transferase-48), 80K-H phosphoprotein (AGE-R2) AGER1/2/3, Galectin-3 (AGE-R3), CD36, and macrophage scavenger receptor (MSR-1 and 2) is implicated in the pathogenesis of diabetic retinopathy [14,22].…”
Section: Advanced Glycation End Products (Ages)mentioning
confidence: 99%